Szepsi Csombor Márton Nürnbergjének forrásai - Buza, János (Gerundium, 2017)
Contribution to the sources of the desciption Nürnberg by Márton Szepsi Csombor. The first travel book in Hungarian – Europica Varietas – was printed in 1620 in the town Kassa, which at that time „Cassovia Superioris Hungariae civitas primaria” was. It is well-known, that Márton Szepsi Csombor read before his travel numbersone geographical and historical books, but he hasn’t mentioned his reading list. It is most probably, that Szepsi Csombor (1595–1622) knew well the descriptions from Conrad Celtis andJohannes Cochlaeus (Brevis Germaniae descriptio, 1512), too. From the sights of Nürnberg he has admired the fine but fortifide castle on the hill, the beautiful stone buildings, the magnificent hospitals, the famous churchyard St. Johannis, the old churches, the market-place, the fine fountain „Schöner Brunnen, and many – but not very expensive – inns. Szepsi Csombor belived, that „Norimberga* is a famous town of repute among all nations.” Finally the Author has mentioned the Altorfiana university and the name ofDr. Remus, who „has* rendred great service to the Hungarian youth and still does.” The critical edition of the complete works of Márton Szepsi Csombor was edited by Sándor Iván Kovács and Péter Kulcsár in Budapest, 1968. The Europica Varietas translated from the Hungarian and with an Introduction by Bernard Adams [Corvina, Budapest 2014] *The quotations were taken over from the Translation of Bernard Adams.